Water-Assisted Synthesis of Zinc- and Copper-Based Metal-Organic Frameworks with Mixed Imidazole Ligands - Dias, Leonardo Francisco Gonçalves [UNESP]; Nunes, Laura Ferreira [UNESP]; Teixeira, Jean Valdir Uchôa [UNESP]; Berenguel, Otávio; Rigolo, Kaue; Bronze-Uhle, Erika Soares [UNESP]; Ramos, Ana Paula; Lisboa-Filho, Paulo Noronha [UNESP] (Springer Nature, 2025)
Metal-organic frameworks (MOFs) have emerged as highly tunable materials with applications from catalysis to biomedical technologies. However, challenges persist in synthesizing stable zinc- and copper-based MOFs. Here, we report an eco-friendly, water-mediated reflux method for preparing Zn and Cu-based MOFs using imidazole and 2-methylimidazole as linkers, achieving yields up to 92% without toxic solvents. Structural characterization revealed crystalline frameworks via X-ray diffraction, while X-ray photoelectron spectroscopy and AFM-IR confirmed that mixed-linker incorporation enhances purity by reducing metal oxidation. Electrochemical studies demonstrated superior stability and adsorption performance, particularly for zinc-based MOFs. These results underscore the potential of mixed-linker strategies to tailor MOF properties for environmental remediation and biomedical applications. Our scalable green synthesis approach offers a promising pathway for optimizing MOFs in emerging technologies.